Learning from the EU Constitutional Treaty : democratic constitutionalization beyond the nation-state - Crum, Ben. (Routledge advances in European politics., 2012)
"The negative results of referenda on the European Union (EU) Constitutional Treaty in France and the Netherlands, and subsequent forced compliance via the Treaty of Lisbon raise complex questions about democratic constitutionalism. This book provides a full analysis of the EU Constitutional Treaty process, grounded in broader political theoretical debates about democratic constitutionalisation and globalization.As international organizations become permanent systems of governance that directly interfere in individuals' lives, it is not enough to have them legitimated by the consent of governments alone. This book presents an evaluation of the present EU Treaty of Lisbon in comparison with the original EU Constitutional Treaty, and analyses the importance of consent of the people, asking if saving the treaty came at the cost of democracy. Drawing first-hand on the referendum in the Netherlands, this book outlines an original political theory of democratic constitutionalisation beyond the nation-state, and argues that international organizations can be put on democratic foundations, but only by properly engaging national political structures. Assessing the EU Constitutional Treaty will be of interest to students and scholars of European Union politics, history and policy"--Provided by publisher.